Unexpected HBsAg decrease after nucleoside analogues retreatment among HBeAg positive postpartum women: a pilot study - Qiao Tang; Chunrui Wang; Hu Li; Zhiwei Chen; Li Zhang; Jing Zhang; Xiaoqing Liu; Yunling Xue; Yue Qiu; Mingli Peng; Yi Zeng; Peng Hu (Virology Journal, 2025)
Abstract Background Mother-to-child transmission (MTCT) is one of the main routes of transmission of HBV, and previous studies focused on the efficacy and safety of nucleoside analogues (NAs) in preventing MTCT. There are limited data on virologic changes of chronic hepatitis B (CHB) patients after discontinuing treatment postpartum and the efficacy of retreatment. Methods A retrospective-prospective real-world pilot cohort study on pregnant women with CHB was conducted. Biochemical and virological characteristics (HBsAg, HBeAg and HBV DNA) in patients received NAs treatment pre-pregnancy (n = 24), patients discontinued treatment after delivery (n = 88) and retreatment patients (n = 22) were collected during follow-up. Results The incidences of HBeAg clearance, half decrease of HBsAg, 0.5 lg decrease of HBsAg and HBsAg < 1000 IU/mL in patients discontinuing treatment postpartum were 5.7% (4/70), 10.0% (8/48), 6.3% (3/48) and 1.6% (1/61), respectively. More significantly decreases of HBsAg, HBeAg and HBV DNA were observed in retreatment patients compared to patients received NAs treatment pre-pregnancy. Significantly higher cumulative incidences of half decrease of HBsAg, 0.5 lg decrease of HBsAg and HBsAg < 1000 IU/mL were achieved in retreatment patients compared to patients received NAs treatment pre-pregnancy. Long-term follow-up results indicated that it is safe for HBeAg positive pregnant patients to discontinue treatment after delivery. Conclusion HBeAg positive patients received NAs treatment during pregnancy and discontinued it postpartum can benefit from NAs retreatment because of unexpected decrease of HBsAg, which may be helpful for achieve the goal of functional cure. Trial registration number ClinicalTrials.gov (No.ChiCTR2100054116).